1962
DOI: 10.3181/00379727-109-27201
|View full text |Cite
|
Sign up to set email alerts
|

Solubility of Bilirubin in Aqueous Solutions.

Abstract: Recent studies concerning the bilirubinbinding properties of serum proteins ( 1 ) have made it necessary to reexamine the solubility of unconjugated bilirubin in aqueous prnteinfree solutions of varying salt concentrations. In dialysis experiments, hIartin( 2 ) noted that only 0.1 mg % bilirubin was soluble in phosphate buffer of ionic strength 0.1. Hy potentiometric titration, Overbeek cf at?. ( 3 ) found that less than 0.5 mg o/o bilirubin was soluble at pH 7.4 in solutions with an ionic strength ranging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

1963
1963
1985
1985

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…The solubility of bilirubin in aqueous solution as reported in the literature also varies widely (6,7,19,29). Utilizing a dialysis method, Martin (19) reported that 0.1 mg/100 ml bilirubin was soluble in 0.1 M phosphate buffer at pH 7.4.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The solubility of bilirubin in aqueous solution as reported in the literature also varies widely (6,7,19,29). Utilizing a dialysis method, Martin (19) reported that 0.1 mg/100 ml bilirubin was soluble in 0.1 M phosphate buffer at pH 7.4.…”
Section: Discussionmentioning
confidence: 99%
“…Although the principle has been generally accepted that the height of the molar extinction coefficient of bilirubin in chloroform at 453 nm is an index of purity of the sample (35), widely varying values have been reported for the maximal visible light absorption wave length and molar absorptivity of bilirubin in aqueous solution (10,19,37,38), human serum albumin solution (14,19,32,33,39), and human sera (2,19,26,32). Similarly, reported values for the "solubility" of bilirubin in aqueous solution have varied widely (6,7,19,29). The reasons for this marked variability in maximal absorption wave length and absorptivity from one laboratory to another remain unclear.…”
Section: Speculationmentioning
confidence: 99%
“…The high apparent pK could be explained if the bilirubin acid is removed from t h e equilibrium either by an internal conformational change o r by aggregation and precipitation. Although there is disagreement as t o the exact solubility of bilirubin at pH 7.4 (7, 8 , 35), it appears that bilirubin solutions exceeding 0.1 pM exist in a supersaturated state (6, 7) and become increasingly unstable as the pH decreases t o 7.0 (8,44). The increased affinity between cells and bilirubin with decreasing pH might simply be explained by the increased hydrophobicity of bilirubin and consequent interaction with lipids and lipoproteins in the cell membranes (3 1).…”
Section: Cell Uptake Of Bilirubinmentioning
confidence: 99%
“…Unconjugated bilirubin is relatively insoluble in aqueous media at physiologic pH (3,4). Although bilirubin is bound to albumin in plasma (5), only small amounts of albumin are present in liver cells (6), and the rate of transfer of bilirubin into liver is greater than the corresponding rate of transfer of albumin (1).…”
Section: Introductionmentioning
confidence: 99%